Reproducibility and Characterization of Head Kinematics During a Large Animal Acceleration Model of Traumatic Brain Injury - Mayer, Andrew R.; Ling, Josef M.; Dodd, Andrew B.; Rannou-Latella, Julie G.; Stephenson, David D.; Dodd, Rebecca J.; Mehos, Carissa J.; Patton, Declan A.; Cullen, D. Kacy; Johnson, Victoria E.; Pabbathi Reddy, Sharvani; Robertson-Benta, Cidney R.; et al. (Frontiers in Neurology, 2021)
Acceleration parameters have been utilized for the last six decades to investigate pathology in both human and animal models of traumatic brain injury (TBI), design safety equipment, and develop injury thresholds. Previous large animal models have quantified acceleration from impulsive loading forces (i.e., machine/object kinematics) rather than directly measuring head kinematics. No study has evaluated the reproducibility of head kinematics in large animal models. Nine (5 males) sexually mature Yucatan swine were exposed to head rotation at a targeted peak angular velocity of 250 rad/s in the coronal plane. Results indicated that measured peak angular velocity of the skull was 51% of the impulsive load, was experienced over a 91% longer duration, and was multi- rather than uni-planar. These findings replicated in a second experiment with a smaller cohort (N=4). The reproducibility of skull kinematics data was mostly within acceptable ranges based on published industry standards, although coefficients of variation (8.9% for peak angular velocity or 12.3% for duration) were higher than impulsive loading parameters produced by the machine (1.1% versus 2.5%, respectively). Immunohistochemical markers of diffuse axonal injury and blood brain barrier breach were not associated with variation in either skull or machine kinematics, suggesting that observed levels of variance in skull kinematics may not be biologically meaningful with current sample sizes. The findings highlight the reproducibility of a large animal acceleration model of TBI, and the importance of direct measurements of skull kinematics to determine the magnitude of angular velocity, refine injury criteria and determine critical thresholds.